2010
DOI: 10.1098/rsbl.2010.0979
|View full text |Cite
|
Sign up to set email alerts
|

Differential outcomes of unilateral interferences at birth

Abstract: ).Behavioural modifications, including modifications of emotional reactivity, can occur following early experience such as handling (manual rubbing). Here, we investigated the effects of unilateral tactile stimulation at an early stage on emotional reactions later on. We handled newborn foals intensively on one side of their body. This early unilateral tactile experience had medium-term effects: the reactions of foals to a human approach, when they were 10 days old, differed according to the side stimulated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Findings from domestic species were concluded to be in accordance with the general pattern [44]. Indeed, the general pattern found in ungulate livestock in the present review still seems to support the emotional valence hypothesis, at least with regard to fear, since vigilance or responses in novel and/ or fear inducing contexts were often found to be directed by the left eye/ ear or right nostril ( [59,67,68,86,96,98,107,114,117,140,144,149,150,166], but see [105,148] for contradictory findings). In contrast, right hemispheric dominance for aggression was only supported by findings in horses [67], while studies on agonistic behavior in cattle and pigs failed to find a bias at the population level [144,172].…”
Section: Emotional Processingsupporting
confidence: 80%
See 2 more Smart Citations
“…Findings from domestic species were concluded to be in accordance with the general pattern [44]. Indeed, the general pattern found in ungulate livestock in the present review still seems to support the emotional valence hypothesis, at least with regard to fear, since vigilance or responses in novel and/ or fear inducing contexts were often found to be directed by the left eye/ ear or right nostril ( [59,67,68,86,96,98,107,114,117,140,144,149,150,166], but see [105,148] for contradictory findings). In contrast, right hemispheric dominance for aggression was only supported by findings in horses [67], while studies on agonistic behavior in cattle and pigs failed to find a bias at the population level [144,172].…”
Section: Emotional Processingsupporting
confidence: 80%
“…The left hemisphere, conversely, may be more sensitive to the negative effects of stress, since high salivary cortisol levels in pigs after tethering correlated negatively to neuron numbers and the volume of the left dentate gyrus [171]. In addition, stress induced by intense tactile stimulation of foals directly after birth increased fear responses to humans at a later age, mostly in foals that were handled from the right side [105], suggesting that the left hemisphere is less able to cope with such stressful events. As mentioned in Section 4.4, different effects of prenatal undernutrition have also been reported.…”
Section: Health Stress and Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…In general it has been shown that there is a right hemisphere cerebral dominance for negatively valenced stimuli (resulting in fear and aggression) and a left hemisphere dominance for positively valenced stimuli such as food or preferred associates (Leliveld et al, 2013). In the horse, asymmetry of visual exploration of negatively, positively or neutrally valenced stimuli was found, with a tendency for left eye exploration (right hemisphere) of negative and right eye exploration for neutral stimuli (De Boyer Des Roches et al, 2008). The tendency to handle horses predominantly from the left side undoubtedly increases the attention paid to stimuli on this side and would contribute to this finding.…”
Section: Appraisal Of Stimuli and Situationsmentioning
confidence: 99%
“…Newborns' lateralized responses can yield information concerning their perception and brain processing of stimuli as shown by numerous animal studies (see a review in Rogers, 2014). A lateralized handling procedure at birth influences foals' subsequent emotional reactions in an approach/contact test; they differ in relation to body side stimulated previously (de Boyer des Roches et al, 2011). The authors hypothesized that sensitivity differed between bodysides inducing different emotional values associated with handling.…”
Section: Promoting Quantitative Behavioral Observationsmentioning
confidence: 99%